Circadian Misalignment Impacts the Association of Visceral Adiposity With Elevated Blood Pressure in Adolescents. Issue 4 (6th March 2023) - Morales-Ghinaglia, Natasha; Larsen, Michael; He, Fan; Calhoun, Susan L.; Vgontzas, Alexandros N.; Liao, Jason; Liao, Duanping; Bixler, Edward O.; Fernandez-Mendoza, Julio
Abstract : Background: Although insufficient sleep has been shown to contribute to obesity-related elevated blood pressure, the circadian timing of sleep has emerged as a novel risk factor. We hypothesized that deviations in sleep midpoint, a measure of circadian timing of sleep, modify the association between visceral adiposity and elevated blood pressure in adolescents. Methods: We studied 303 subjects from the Penn State Child Cohort (16.2±2.2 years; 47.5% female; 21.5% racial/ethnic minority). Actigraphy-measured sleep duration, midpoint, variability, and regularity were calculated across a 7-night period. Visceral adipose tissue (VAT) was measured with dual-energy X-ray absorptiometry. Systolic blood pressure (SBP) and diastolic blood pressure levels were measured in the seated position. Multivariable linear regression models tested sleep midpoint and its regularity as effect modifiers of VAT on SBP/diastolic blood pressure levels, while adjusting for demographic and sleep covariables. These associations were also examined as a function of being in-school or on-break. Results: Significant interactions were found between VAT and sleep irregularity, but not sleep midpoint, on SBP ( P interaction=0.007) and diastolic blood pressure ( P interaction=0.022). Additionally, significant interactions were found between VAT and schooldays sleep midpoint on SBP ( P interaction=0.026) and diastolic blood pressure ( P interaction=0.043), whereas significant interactions were found between VAT and on-break weekdays sleep irregularity on SBP ( P interaction=0.034). Conclusions: A delayed and an irregular sleep midpoint during school and during free-days, respectively, increase the impact of VAT on elevated blood pressure in adolescents. These data suggest that deviations in the circadian timing of sleep contribute to the increased cardiovascular sequelae associated with obesity and that its distinct metrics require measurement under different entrainment conditions in adolescents.